THE INFLUENCE OF TECHNOLOGY GLOBALIZATION CHANGES THE ORDER INTO A SHOWCASE - SRI BUDI RAHARJO; SUNNY UMMUL FIRDAUS (CV KULTURA DIGITAL MEDIA, 2024)
Every country certainly has rules to regulate behavior in society or its people, this is related to human nature that humans are homohominilupus (humans are wolves to other humans) meaning that humans have an innate/natural nature, namely predators for other humans and have a competitive nature and will be able to influence others and can influence others for personal interests with their egos, One of the major influences and impacts on significant social change is IA (Artificial Intelligence) technology or what in Indonesia is often called artificial intelligence. This influence is very easy and fast to enter society because humans are social creatures who cannot live without other people. The history of the emergence of globalization did not occur quickly but through a very long process and which continuously involves social change, including the economic, cultural and political fields that exist. The current situation that we are feeling is the globalization of culture in which we really feel the social changes, where the spread of culture such as music and lifestyle including fake and online gambling and online trading, local wisdom and our nation's culture are very different from the culture of foreigners, manners, manners, behavior and way of dressing, how to speak are very prioritized, especially as our country is a country based on Pancasila, with current technology, little by little our local wisdom has begun to change, where people no longer prioritize conscience but prioritize ego. so that we can feel the feeling of courage and self-defeating nature in this power, such as the loss of a sense of justice, benefits and certainty of the law.